2022
DOI: 10.1021/acsomega.2c01115
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insight into the Hydration States of Layered Double Hydroxides

Abstract: Effective protective coatings are an essential component of lightweight engineering materials in a large variety of applications as they ensure structural integrity of the base material throughout its whole service life. Layered double hydroxides (LDHs) loaded with corrosion inhibitors depict a promising approach to realize an active corrosion protection for aluminum and magnesium. In this work, we employed a combination of density functional theory and molecular dynamics simulations to gain a deeper understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 85 publications
1
14
0
Order By: Relevance
“…Interlayer water molecules have an important influence on the structure and swelling properties of LDHs, and so, hydration energy is used to analyze the effect of introducing water molecules on the structure and properties of LDHs. The hydration energy is defined , as follows normalΔ U normalH = U ( N w ) U ( 0 ) n where n is the total number of water molecules, U ( N w ) is the total potential energy of the system, and U (0) is the total potential energy of the system when there are no water molecules. This equation can easily and effectively calculate the hydration energy of interlayer water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interlayer water molecules have an important influence on the structure and swelling properties of LDHs, and so, hydration energy is used to analyze the effect of introducing water molecules on the structure and properties of LDHs. The hydration energy is defined , as follows normalΔ U normalH = U ( N w ) U ( 0 ) n where n is the total number of water molecules, U ( N w ) is the total potential energy of the system, and U (0) is the total potential energy of the system when there are no water molecules. This equation can easily and effectively calculate the hydration energy of interlayer water.…”
Section: Resultsmentioning
confidence: 99%
“…Interlayer water molecules have an important influence on the structure and swelling properties of LDHs, and so, hydration energy is used to analyze the effect of introducing water molecules on the structure and properties of LDHs. The hydration energy is defined 32,51 as follows…”
Section: Interlayer Hydration and Stability 331 Interlayer Hydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we prepared two model LDH structures with highly charged [Mg 0.66 Al 0.33 (OH) 2 ] layers and weakly charged [Mg 0.833 Al 0.166 (OH) 2 ] layers to analyse the above-described experimental results. Second, the interlayer binding energies, the hydrogen-bonding structure associated with the orientation of interlayer anions and water molecules, and the interlayer distance 38 for both LDHs with various interlayer anion compositions ( x B ) were calculated as a function of the interlayer water content ( m ). The structure with x B = 0.125 in highly charged LDHs and the structure with x B = 0.25 in weakly charged LDHs were employed to investigate the intermediate interlayer structures during the nitrate ion storage.…”
Section: Resultsmentioning
confidence: 99%
“…[173,174] All the necessary parameters and inputs to carry out the MD simulations are available online. [175] This MD procedure has already been employed by other researchers to understand the structure and processes involving LDHs for different applications, [136,[176][177][178] and was employed in our research group, together with in-house tools, [179] to unveil the acid-base equilibrium, conformation and degree of solvation inside the interlayer galleries of an LDH material intercalating a well-known corrosion inhibitor, 2-mercaptobenzothiazole (MBT). [180] LDH-MBT is a nanostructured coating additive [181] and it was demonstrated that MD simulations can provide insights into the structural characterization performed by powder X-ray diffraction and the processes behind the weight loss indicated by thermogravimetric analysis.…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%